2019
DOI: 10.1186/s12874-019-0889-3
|View full text |Cite
|
Sign up to set email alerts
|

Reporting guideline for priority setting of health research (REPRISE)

Abstract: BackgroundResearch priority setting with stakeholders can help direct the limited resources for health research toward priority areas of need. Ensuring transparency of the priority setting process can strengthen legitimacy and credibility for influencing the research agenda. This study aims to develop a reporting guideline for priority setting of health research.MethodsWe searched electronic databases and relevant websites for sources (frameworks, guidelines, or models for conducting, appraising, reporting or … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 46 publications
2
138
0
4
Order By: Relevance
“…On a special note, the priority of palliative care at home was integrated as part of phase III community-based services, not as a stand-alone research priority need. The process of research priority setting was complex due to multiple engagement phases, however the use of participatory approach underpinned by PPI principles enabled us to identify, address and integrate the diverse stakeholders values and perspectives 33 throughout the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a special note, the priority of palliative care at home was integrated as part of phase III community-based services, not as a stand-alone research priority need. The process of research priority setting was complex due to multiple engagement phases, however the use of participatory approach underpinned by PPI principles enabled us to identify, address and integrate the diverse stakeholders values and perspectives 33 throughout the process.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is a significant variation in the use of research priority-setting methodology worldwide, there is no gold standard or best practice for evaluating the process of research priority setting 35 . For this research priority setting exercise we didn’t follow any checklist as part of the project design and engagement process; however, we came across REPRISE checklist and guidelines 33 and tried to refer this guide to facilitate comprehensive and transparent reporting of health research priority-setting exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Results were reported using the REporting guideline for PRIority SEtting of health research (REPRISE) guidelines. 11 (online supplemental file 1)…”
Section: Methodsmentioning
confidence: 99%
“…The complete research priority setting exercise was reported using the REPRISE checklist and guidelines. 25 Patient and public involvement Patients, family members and the wider social care sector were involved in every aspect of the priority setting exercise. We had input at a strategic level from two patient representatives on the WKRU executive board who supported the idea of an All Wales priority setting exercise in health services and social care.…”
Section: Workhop 2: Setting Priorities With the Welsh Renal Clinicalmentioning
confidence: 99%